Pengaruh Sistem Manajemen Lingkungan dan Manajemen Aset terhadap Kinerja Keuangan: Studi Kasus pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2019-2022 - Qaira, Miftahul; Deviani, Deviani (Universitas Negeri Padang, 2025)
This study aims to determine the simultaneous and partial effect of environmental management systems, asset management, on financial performance in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the period 2019-2022. The operationalization variables in this study are financial performance as the dependent variable, while the environmental management system, asset management, as the independent variables. This study aims to determine the simultaneous and partial effect of environmental management systems, asset management, on financial performance in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the period 2019-2022. The operationalization variables in this study are financial performance as the dependent variable, while the environmental management system, asset management, as the independent variables. The results of this study indicate that simultaneously the environmental management system, asset management, has an influence on financial performance. Partially the environmental management system does not affect financial performance, and asset management has a positive effect on financial performance. This research can help companies as input and considerations to evaluate financial performance by knowing the factors that can influence it.